Diagnostic value of C-reactive protein/ albumin ratio and TMTC1 in intracranial atherosclerotic stenosis in patients with acute cerebral infarction - Jinping Mo; Lin Liu; Zhe Li; Zongji Hu; Yuan Tan; Gen Long (Scientific Reports)
Abstract We retrospectively analyzed the degree of stenosis in patients with acute cerebral infarction (CI) to investigate the correlation between C-reactive protein (CRP)/ albumin ratio and intracranial atherosclerotic stenosis (ICAS). Meanwhile, the differentially expressed genes (DEGs) in CI were identified through two Microarray profile GSE202518 and GSE180470. The receiver operating characteristics (ROC) curve analysis were performed to evaluate the sensitivity and specificity of CRP/ albumin ratio for the diagnosis of ICAS. Binary logistic regression models were used to examine the relationship between these biomarkers and the degree of ICAS, adjusting for potential confounders. The level of CRP/ albumin ratio in high group was significantly higher than that in low group. The area under the curve (AUC) of CRP/ albumin ratio for the diagnosis of ICAS was 0.6526 (95% CI, 0.5737 to 0.7316) in serum. TMTC1 was found to be highly expressed in high group, and the AUC of TMTC1 for the diagnosis of ICAS was 0.6853 (95% CI, 0.6085 to 0.7622) in serum. Moreover, the combination of CRP/ albumin ratio and TMTC1 enhanced the diagnosis of ICAS with AUC of 0.708 (95% CI, 0.633 to 0.783). High levels of CRP/ albumin ratio and TMTC1 expression were associated with the degree of ICAS, and may be potential diagnostic and prognostic markers for the ICAS.